An optimal area approach to intercomparing polarimetric radar rain-rate algorithms with gauge data - Bringi, V. N., author; Bolen, S., author; Chandrasekar, V., author; American Meteorological Society, publisher (Colorado State University. Libraries, 1998)
An optimal area method is described that is used as a basis for comparing KDP-, (KDP, ZDR)-, and Zh-based estimates of rain rates with gauge-measured rain rates. The location and dimensions of an elliptically shaped optimal area within the radar scan area surrounding the gauge are determined objectively via an rms error minimization of the difference between the KDP-based radar estimate and gauge data and via use of the spatial structure of the rms difference field itself. Four convective events were analyzed with rain rates in the range of 20-120 mm h-1, with two of the events containing marble-sized hail. The analysis shows that excellent results could be achieved using KDP-based rain-rate estimators.